Peer effects and social preferences in voluntary cooperation - Christian Thöni; Simon Gächter (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2011)
Substantial evidence suggests the behavioral relevance of social preferences and also the importance of social influence effects ("peer effects"). Yet, little is known about how peer effects and social preferences are related. In a three-person gift-exchange experiment we find causal evidence for peer effects in voluntary cooperation: agents' efforts are positively related despite the absence of material payoff interdependencies. We confront this result with major theories of social preferences which predict that efforts are unrelated, or negatively related. Some theories allow for positively-related efforts but cannot explain most observations. Conformism, norm following and considerations of social esteem are candidate explanations.
Keywords: C92; D03; 330; social preferences; voluntary cooperation; peer effects; reflection problem; gift-exchange; conformism; social norms; social esteem; Soziale Gruppe; Soziale Wohlfahrtsfunktion; Test; Soziale Norm; Normbefolgung